2006
DOI: 10.1093/cercor/bhl100
|View full text |Cite
|
Sign up to set email alerts
|

Dissociated Neural Mechanisms for Face Detection and Configural Encoding: Evidence from N170 and Induced Gamma-Band Oscillation Effects

Abstract: Despite ample research, the structure and the functional characteristics of neural systems involved in human face processing are still a matter of active debate. Here we dissociated between a neural mechanism manifested by the face-sensitive N170 event-related potential effect and a mechanism manifested by induced electroencephalographic oscillations in the gamma band, which have been previously associated with the integration of individually coded features and activation of corresponding neural representation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
84
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 43 publications
11
84
1
1
Order By: Relevance
“…Although recognition of face identity was not requested in our task, it is likely that, at least on many trials, participants did in fact recognise the famous faces they were shown. If that were the case, N1 could reflect perceptual evidence of face presentation in ventral face-specific areas during a first processing step-previously termed as structural encoding (Zion-Golumbic & Bentin, 2007;Bentin & Deouell, 2000)-whereas N2 could signal access to a specific face representation in a second step (Bentin & Deouell, 2000). A similar idea has been recently proposed by Nasr and Esteky (2009).…”
Section: Discussionmentioning
confidence: 72%
“…Although recognition of face identity was not requested in our task, it is likely that, at least on many trials, participants did in fact recognise the famous faces they were shown. If that were the case, N1 could reflect perceptual evidence of face presentation in ventral face-specific areas during a first processing step-previously termed as structural encoding (Zion-Golumbic & Bentin, 2007;Bentin & Deouell, 2000)-whereas N2 could signal access to a specific face representation in a second step (Bentin & Deouell, 2000). A similar idea has been recently proposed by Nasr and Esteky (2009).…”
Section: Discussionmentioning
confidence: 72%
“…Directed attention reliably increases GBA and concomitantly decreases lower frequencies in the alpha (8e12 Hz) and beta (13e30 Hz) band (Fries, Reynolds, Rorie, & Desimone, 2001;Jensen, Kaiser, & Lachaux, 2007;Ossand on et al, 2012;Siegel, Donner, Oostenveld, Fries, & Engel, 2008). GBA has been related to the perception (Rodriguez et al, 1999) and structural encoding of faces (Gao et al, 2013;Zion-Golumbic & Bentin, 2007). Furthermore, processing emotional compared to neutral facial expressions elicited power changes in the delta (.5e4 Hz), theta (4e8 Hz), and gamma band (Balconi & Lucchiari, 2006;Balconi & Pozzoli, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies have shown that N170 components triggered by scrambled faces tend to be enhanced and delayed relative to the N170 in response to intact faces (e.g. Bentin et al, 1996;Zion-Golumbic & Bentin, 2007; for similar N170 modulations caused by other disruptions of the canonical facial configuration, see Letourneau & Mitchell, 2008;Jacques & Rossion, 2010). The fact that face inversion and the spatial scrambling of facial features have similar effects on the N170 emphasize the sensitivity of this N170 component to deviations from a canonical upright face templates, and suggests that these two manipulations may affect the same stages of configural face processing.…”
Section: The N170 Component Reveals Atypical Configural Face Processimentioning
confidence: 99%